Islamic Educational Psychology and Feminism: An Epistemological Approach to Gender Equity in Education - Yazid Al Ansori; Tutukningsih; Kholid Mawardi (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: The purpose of this study is to determine an epistemology of Islamic educational psychology through the spirit of feminism in responding to gender-biased educational practices. Novelty: This research combines feminist theory with Islamic educational psychology, offering a transformative paradigm that has rarely been explored in previous research. Methods: This study uses a qualitative approach. The data sources were obtained by analyzing various existing literature, both from books and scientific journals. Results: The results of this study indicate that Islamic educational psychology can elevate the dignity of women's rights, the spirit of feminism is met with the spirit of Islam in developing education that upholds equality. Through an approach that combines the spirit of feminism with Islamic educational psychology, this study offers a new paradigm that is inclusive and equal. Conclusion: This approach emphasizes curriculum reform, teacher empowerment, and the implementation of affirmative policies as real steps to eliminate gender bias. By involving all elements of society, including religious figures and academics, it is hoped that cultural and policy changes can be achieved sustainably.